THE FULFILLMENT OF THE RIGHTS OF SUSPECTS AND THE ACCUSED IN THE CRIMINAL JUSTICE PROCESS - Sunarta, I Made (Journal of Humanity, 2014)
This research aims to know the fulfillment of the rights of the suspect and the defendant the process of criminal justice in the city of Makassar and obstacles faced in giving the law enforcement apparatus fulfillment for the suspect and the accused as the fulfillment of human rights for suspects in Makassar city. Implementation of the fulfillment of the rights of suspects and defendants have done well, especially in terms of rights provides information, right to obtain health services, and the right to get visits. But there are some rights that is still less than optimal due to several obstacles, i.e. the right to legal assistance and the right to conduct worship for suspects and defendants. Constraints faced by the authorities in terms of the fulfillment of the rights of suspects and accused persons referred to in the conclusions of the first is in terms of the fulfillment of the right to legal assistance, the refusal by a suspect, fearing it will cost you, the lack of number of Advocates in Makassar city, led to the granting of legal aid less than optimal, and the lack of Government attention to the legal counselling activities in the home countrys Arrest Class I Makassar. In terms of the fulfillment of the right to conduct worship services, the lack of human resources available either at Police Resort Cities of Makassar and in State Custody Homes Class Makassar that HE was able to furnish the activities become acts of worship in terms of ustadz and clergy unable to attend religious worship activities to fill. And there are a number of suspects and accused persons who do not want to communicate by the apparatus, so it makes the apparatus difficulty experienced in conducting worship rights for the fulfilment of the suspect and the accused.